CORPORATE SOCIAL RESPONSIBILITY PRACTICES IN MSMES: BUSINESS OWNERS’ PERSPECTIVES THROUGH A PHENOMENOLOGICAL APPROACH - Muhammad; Lilik Purwanti; San Rudiyanto (ZILLZELL MEDIA PRIMA, 2026)
This study aims to describe how MSME owners understand the concept of corporate social responsibility (CSR) and how this understanding relates to their practices. To explore the meaning, experiences, and interpretations of CSR by business actors, this study employs a phenomenological approach and an interpretive paradigm as a lens for addressing the research problem. This approach was chosen because it enables researchers to gain an in-depth understanding of the subjective experiences of MSME owners, including the values, beliefs, and considerations that shape their actions. The findings reveal that MSME owners' understanding of CSR is generally confined to informal social relationships, such as assisting neighbors, contributing to community activities, or maintaining good relations with the surrounding environment. CSR is not yet perceived as part of a structured business strategy nor as an ongoing responsibility inherent to business operations. Moreover, resource constraints including limitations in time, labor, and financial capacity emerge as key factors restricting CSR implementation at the MSME level. Business owners tend to prioritize the continuity of daily operations, leading them to view CSR activities as additional efforts undertaken only when circumstances allow.